Suitability of Mahseer Tor putitora (Hamilton) in Polyculture with Indian Major Carps - Rahman, MR; Rahman, MS; Khan, MGQ; Mostary, S (Progressive Agriculture, 2014)
An experiment on polyculture of mahseer with Indian major carps at same stocking density was carried out for a period of 10 months from February 1 to December 1, 2004 in six experimental ponds. There were three treatments with two replicates each. Treatment 1 was designed with catla (Catla catla), rohu (Labeo rohita) and mrigal (Cirrhinus mrigala), treatment 2 with catla (Catla catla), rohu (Labeo rohita) and mahseer (Tor putitora) while treatment 3 with catla (Catla catla), rohu (Labeo rohita), mrigal (Cirrhinus mrigala) and mahseer (Tor putitora). Mahseer of the treatment 2 was introduced instead of mrigal of treatment 1 and 50% of mrigal was replaced with mahseer in treatment 3. The stocking density in all the treatments was 30 fish/decimal (7500 fish/ha). The feeds were supplied at the rate of 3-7% of the body weight of fish. The gross and net productions recorded were 5362.78 and 5188.64, 5431.42 and 5262.32, 5357.11 and 5528.74 kg/ha/yr in treatments 1, 2 and 3 respectively. Though there was no significant difference (p>0.05) among the three treatments using ANOVA but the production in treatment-3 was slightly higher than treatments 1 and treatment 2. However, there was no negative effect of mahseer on the growth and production of Indian major carps. So, it can be concluded that polyculture of mahseer with Indian major carps (catla, rohu and mrigal) can be done in ponds. DOI: http://dx.doi.org/10.3329/pa.v18i2.18194 Progress. Agric. 18(2): 175 - 182, 2007